Analisis Komunikasi Platform Internet of Things Aplikasi Blynk - Puji Utami Rakhmawati; Rizdania; Sumantri (Prosiding Seminar Nasional Teknoka, 2024)
The development of the Internet of Things (IoT) has led to the birth of various platforms that enable real-time management and control of devices. One of the prominent platforms is Blynk, an application that provides two-way communication between IoT devices and users through mobile applications. This study aims to analyse the communication mechanism in the Blynk application, including the protocols used, the efficiency of data transmission, and the level of security applied. Through this study, it is analysed how Blynk communicates with various microcontroller devices such as ESP32 and ESP8266 using TCP/IP, HTTP, and MQTT protocols. In addition, this study also evaluates the level of data encryption through SSL/TLS protocols to ensure communication security in an IoT environment. By conducting experiments on IoT devices connected through the Blynk network, this research found that Blynk is able to provide responsive and secure communication, with minimal bandwidth consumption.